Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Pada UPT. ABC Koto Masjid Village, XIII Koto Kampar - Saputri Intan; Saiful Anuar (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
The purpose of this study was to determine the Influence of the Work Environment, Employee Performance, at the Fisheries Processing Unit of Koto Masjid Village, XIII Koto Kampar District. The population in this study was 91 employees and all were sampled. The research method used was the Descriptive method with a Quantitative approach. The average score for the overall Statement about the work environment was 4.08, meaning that the respondent's answer to the statement about the work environment was agree. While the tester's answer to the statement of employee performance was an average of 4.30, which means that they strongly agree. The data analysis used was simple linear regression with the results of the ESETESA diretelch, namely Y = 15.990 + 0.559X which has a positive relationship direction, namely if the work environment variable increases, the employee performance variable will increase. Based on the results of the t-test, it was obtained that the Dibung value was 7.414 > table 1.986 with a significant level of 0.00 < 0.05. This means that the work environment has a positive and significant effect on employee performance at the UPT. Fishery Product Processing in Koto Masjid Village, XIII Koto Kampar District. The R Square value of 0.382 or 38.2% means that the environmental variables of Kezia have an influence on employee performance of 38.2%. While the remaining 61.8% is explained by other variables that are not included in the model. Thus it can be seen that there are still many other factors that influence the work environment.